Medial gastrocnemius muscle–tendon unit ratios of young females and males. (September 2022) - Tennler, Janina; Hahn, Daniel; Raiteri, Brent J.
Abstract: A muscle's contractile element length relative to its muscle–tendon unit (MTU) length is a fundamental design feature affecting MTU function, with high (0.9) or low ratios (0.1) favouring either rapid or economical force production, respectively. Despite the importance for MTU function, little in vivo work has been done to understand contractile element-MTU length ratio variability between individuals and sexes. We therefore compared the medial gastrocnemius (MG) MTU ratios of thirteen females and eighteen males, and explored whether individual ratios could be predicted based on anatomical features. At the presumed tendon slack length ankle joint angle, lengths of MG's MTU, Achilles tendon, muscle belly and its muscle fascicles were measured from B-mode ultrasound images. Contractile element length was represented by the in-series muscle fascicle length (FL) and was calculated by multiplying FL by the cosine of fascicle angle. The mean ± standard deviation in-series FL-MTU length ratio was 0.09 ± 0.02 and ranged from 0.06 to 0.11, whereas the muscle belly length-MTU length ratio was 0.54 ± 0.38 and ranged from 0.47 to 0.60. Neither ratio was significantly different between females and males ( p  ≥ 0.116). In-series FL was not significantly correlated with MTU length ( r  = -0.115, p  =.538), muscle belly length ( r  = 0.05, p  =.788), or shank length ( r  = 0.169, p  =.364), but MTU length was significantly correlated with muscle belly length ( r  = 0.641, p  <.001), and shank length ( r  = 0.575, p  =.001). A low in-series FL-MTU length ratio suggests that the MG of young, healthy individuals is specialised for energy-efficient stretch–shortening cycles. These findings provide useful inputs for the MTU actuator design of Hill-type models.